Palliative Care for the Asian American Adult Population: A Scoping Review. (June 2021) - La, In Seo; Lee, Mei Ching; Hinderer, Katherine A.; Chi, Iris; Liu, Ruotong; Liu, Mandong; Fu, Yunting
Background: The Asian American (AA) population is rapidly becoming one of the largest racial/ethnic groups in the United States. Despite this growth and advances in palliative care (PC) programs in the United States, the scope and nature of the literature regarding PC for AAs remains unclear. This review provides an overview of existing research on PC for AAs, identifies gaps in the research with recommendations for future research and delineates practice implications. Methods: A scoping review of studies published in English was conducted. Electronic Databases (PubMed, Embase, CINAHL, and PsycINFO databases) were searched up to December 2019. No starting date limit was set. Arksey and O'Malley's methodological framework was followed for scoping reviews. Results: Of 2390 publications initially identified, 42 studies met our inclusion criteria for this review. Southeast AA subgroups remain understudied compared to East and South AAs. Most studies were descriptive; a few (n = 3) evaluated effectiveness of PC interventions for AAs. Research synthesized in this review addresses the following topics and includes considerations in PC related to care recipients and their relatives: treatment choice discussions (73%), coordination of care with health care providers (26%), symptom management (14%), and emotional support (10%). This review identified various factors around PC for AAs, specifically the influence of cultural aspects, including levels of acculturation, traditional norms and values, and religious beliefs. Conclusion: A culturally inclusive approach is vital to providing appropriate and accessible PC for AAs. Further research is needed concerning core PC components and effective interventions across diverse AA subgroups.